IgE-mediated allergy to Lepidoglyphus destructor in an urban population - an epidemiologic study - Gislason, D; Gislason, T (Allergy, 2010)
To access publisher full text version of this article. Please click on the hyperlink in Additional Links field BACKGROUND: The aim of this study was to estimate the prevalence of IgE-mediated allergy to Lepidoglyphus destructor and its clinical importance in Reykjavik, Iceland. METHODS: All Icelandic participants in the European Community Respiratory Health Survey in Reykjavik and suburbs were skin prick tested (SPT) for L. destructor. They also participated in a structured interview including questions about exposure to hay and symptoms related to hay exposure. Spirometry and methacholine tests were also performed. RESULTS: Altogether, 540 individuals underwent SPT with 12 allergens. Among them, 137 (25.4%) had positive skin tests, defined as at least one mean wheal reaction of > or =1 mm. By this definition, 34 (6.3%) were positive to L. destructor. These 34 individuals were significantly (P < 0.001) more often allergic to D. pteronyssinus (24/34), grass (14/34), cat (13/34), dog (12/34), Alternaria (11/34), Cladosporium (9/34), horse (8/34), and olive (8/34) than those not allergic to L. destructor. Those SPT positive to L. destructor had a higher total IgE (geometric mean: 40.9 kU/I vs 12.3 kU/I, P < 0.001) than those who were negative to L. destructor, but their lung function was comparable to that of the others. Asthma during the preceding 12 months or asthma ever suffered was not overrepresented among those SPT-positive to L. destructor. Individuals with symptoms associated with hay exposure were more often SPT positive to L. destructor than those not having symptoms (P < 0.01). CONCLUSIONS: In a random urban population, 6.3% showed IgE-mediated allergy to L. destructor. These were often polysensitized atopics with a high prevalence of clinical symptoms associated with exposure to hay.